Challenges in the electrochemical compression of an ammonia-hydrogen blend. (3rd November 2021) - Chouhan, Ashish; Aryal, Utsav R.; Sivakumar, Premanand O.; Bahar, Bamdad; Prasad, Ajay K.
Abstract: Ammonia is widely used in fertilizers and cleaning products, as a refrigerant in air conditioning, and in food preservation. Ammonia is also an excellent vector for hydrogen with high energy density and can be compressed for convenient transport and storage. In this paper, we examine the suitability of ammonia for electrochemical compression (ECC). Electrochemical compressors can be an ideal replacement for mechanical compressors because of noiseless operation and higher efficiencies. They also permit the use of environmentally-friendly refrigerants such as ammonia. We evaluate the performance of an ECC operated on an ammonia-hydrogen blend using a fuel cell type hardware. A perfluorosulfonic acid (PFSA) membrane is employed to facilitate the pumping of ammonia, using hydrogen as a carrier gas, by the conduction of N H 4 + ions from anode to cathode. We have recently established and experimentally validated a robust formulation for the electrochemical compression of hydrogen that properly addresses the role of back-diffusion. The primary goal of this work is to assess the effect of back-diffusion during the ECC of ammonia. Our results indicate that back-diffusion plays a highly deleterious role when a PFSA membrane is employed and is the principal challenge that needs to be addressed during the ECC of ammonia-hydrogen blends. Highlights: Electrochemical compression of NH3 /H2 blend conducted with Nafion membrane. Composition of pressurized cathode outlet gas analyzed by Nessler's method. NH3 and H2 permeability coefficients measured by depressurization experiments. The permeability of NH3 is three orders larger than that of H2 . Back-diffusion is the primary challenge during ECC of ammonia.